2022
DOI: 10.1200/jco.21.01497
|View full text |Cite|
|
Sign up to set email alerts
|

First-Line Immunotherapy for Non–Small-Cell Lung Cancer

Abstract: For patients with metastatic non–small-cell lung cancer (mNSCLC), the last decade has been characterized by critical progress that has contributed to substantially improved survival. In particular, the development of specific antibodies against the programmed death (PD-1) receptor, programmed death-ligand 1 (PD-L1), and the cytotoxic T-lymphocyte–associated protein 4 receptor in the therapeutic strategy of mNSCLC either in first- or in second-line settings have led to unprecedented prolonged survival for a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
312
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 499 publications
(315 citation statements)
references
References 69 publications
2
312
0
1
Order By: Relevance
“…Currently, nearly all patients with metastatic NSCLC receive anti-PD-1/PD-L1 therapy in first-line setting except for the metastatic NSCLC harboring targetable oncogenes 52 . Re et al revealed that the level of sEV PD-L1 changed in NSCLC patients receiving nivolumab and pembrolizumab 51 .…”
Section: The Role Of Sev Pd-l1 In Cancer Immunotherapymentioning
confidence: 99%
“…Currently, nearly all patients with metastatic NSCLC receive anti-PD-1/PD-L1 therapy in first-line setting except for the metastatic NSCLC harboring targetable oncogenes 52 . Re et al revealed that the level of sEV PD-L1 changed in NSCLC patients receiving nivolumab and pembrolizumab 51 .…”
Section: The Role Of Sev Pd-l1 In Cancer Immunotherapymentioning
confidence: 99%
“…Currently, the first-line treatment in daily practice of patients with KRAS -mutated tumors associates ICIs (pembrolizumab) and chemotherapy or immunotherapy (pembrolizumab) alone for tumors expressing PD-L1 in more than 50% of tumor cells [ 7 , 178 ]. A therapeutic strategy using specific KRAS inhibitors alone might be administered in the near future as first-line treatment for tumors expressing PD-L1 in less than 50% of tumor cells [ 23 , 30 , 129 , 130 ].…”
Section: Impact Of Kras Mutations On the Efficienc...mentioning
confidence: 99%
“…Among the lung cancer histological subtypes, non-small cell lung carcinoma (NSCLC) is the most frequent histological subtype, representing at least 85% of all cases [ 5 ]. The therapeutic strategy of advanced-stage or metastatic NSCLC, notably of non-squamous (NS)-NSCLC, has evolved dramatically in the last few years, thanks to the development of new targeted therapies and immune checkpoint inhibitors (ICIs) administered alone or in association with chemotherapy and targeted therapies [ 6 , 7 , 8 ]. These different therapies have significantly increased the overall survival of NS-NSCLC patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harnessing immune response to attack tumor cells has proven to be a successful treatment strategy against advanced thoracic malignancies. This immune checkpoint blockade (ICB) strategy with anti-PD-(L)1 and anti-CTLA4 monoclonal antibodies has reported durable responses and has significantly improved the overall survival rates either as monotherapy in selected tumors, or as a combination with immunotherapy and/or chemotherapy in all thoracic malignancies, except thymic epithelial tumors (TET) (1)(2)(3). PD-L1 expression in tumor cells is the most robust predictive biomarker for the efficacy of the ICB strategy.…”
Section: Understanding the Interplay Between The Tumor Immune Microen...mentioning
confidence: 99%